1998
DOI: 10.1038/sj.bmt.1701278
|View full text |Cite
|
Sign up to set email alerts
|

Donor leukocyte infusion for treatment of graft rejection post partially mismatched related donor bone marrow transplant

Abstract: Summary:Graft rejection following bone marrow transplantation is more common in patients who receive their grafts from alternative donors and whose marrow is T cell depleted. Rejection in these patients is mediated by persistent host cells that interfere with successful establishment of donor-derived hematopoietic recovery. We describe a patient with chronic myelogenous leukemia in accelerated phase who rejected a T cell-depleted bone marrow graft, 2 months following partially mismatched related donor bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…A relative paucity of data exists in the literature regarding experience administering haplocompatible DLI, and the informative reports are summarized in Table 3. 1,[6][7][8][9][10] In addition to those listed in Table 3, several other reports exist. Kawano et al 20 describe administration of an unknown dose of prophylactic G-CSF-mobilized haplocompatible DLI to four pediatric patients, all of whom developed Grade I to Grade IV GVHD and ultimately expired from relapse or infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A relative paucity of data exists in the literature regarding experience administering haplocompatible DLI, and the informative reports are summarized in Table 3. 1,[6][7][8][9][10] In addition to those listed in Table 3, several other reports exist. Kawano et al 20 describe administration of an unknown dose of prophylactic G-CSF-mobilized haplocompatible DLI to four pediatric patients, all of whom developed Grade I to Grade IV GVHD and ultimately expired from relapse or infection.…”
Section: Discussionmentioning
confidence: 99%
“…5 The optimal safe dose of DLI that can be administered in the haplocompatible setting is less clear, as only a few reports with small numbers of patients exist on the administration of haplocompatible DLI. 1,[6][7][8][9][10] The source of the T cells utilized for haplocompatible DLI may be important in terms of eventual outcome because of the toleragenic influence of G-CSF on T-cell function. 11 In some reports it is clear that the DLI originated from the cryopreserved CD34À fraction following processing of G-CSF-mobilized PBSC, 9 whereas in other reports the DLI appears to have been obtained from nonmobilized blood collected from the donor after HSCT, [6][7][8] or is not specified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GVH effect exerted by donor lymphocytes can also be exploited to enhance defective engraftment [45], by displacing residual host haemopoiesis, and to facilitate the reconstitution of the immune system after transplant. In patients who become PCR negative following DLI, two patterns of response have been observed.…”
mentioning
confidence: 99%
“…Donor lymphocyte infusion has been used for dissolution of unstable mixed chimerism in recipients of many malignant and nonmalignant hematopoietic diseases after BMT. [2][3][4][5] However, this effect of DLI has rarely been successful in thalassemia major. Aker et al 2 reported that a patient with thalassemia and unstable mixed chimerism after BMT was successfully treated with DLI to attain complete donor-derived reconstitution of the residual hematopoietic host cells.…”
mentioning
confidence: 99%